Arsenic trioxide potentiates Gilteritinib-induced apoptosis in FLT3-ITD positive leukemic cells via IRE1a-JNK-mediated endoplasmic reticulum stress - Xiaoli Hu; Jiayi Cai; Jianyi Zhu; Wenjing Lang; Jihua Zhong; Hua Zhong; Fangyuan Chen (Cancer Cell International, 2020)
Abstract Background Acute myeloid leukemia (AML) patients with FMS-like tyrosine kinase 3-internal tandem duplication (FLT3-ITD) have a high relapse rate and poor prognosis. This study aims to explore the underlying mechanism of combining Gilteritinib with ATO at low concentration in the treatment of FLT3-ITD positive leukemias. Methods We used both in vitro and in vivo studies to investigate the effects of combination of Gilteritinib with ATO at low concentration on FLT3-ITD positive leukemias, together with the underlying molecular mechanisms of these processes. Results Combination of Gilteritinib with ATO showed synergistic effects on inhibiting proliferation, increasing apoptosis and attenuating invasive ability in FLT3-ITD-mutated cells and reducing tumor growth in nude mice. Results of western blot indicated that Gilteritinib increased a 160KD form of FLT3 protein on the surface of cell membrane. Detection of endoplasmic reticulum stress marker protein revealed that IRE1a and its downstream signal phosphorylated JNK were suppressed in Gilteritinib-treated FLT3-ITD positive cells. The downregulation of IRE1a induced by Gilteritinib was reversed with addition of ATO. Knockdown of IRE1a diminished the combinatorial effects of Gilteritinib plus ATO treatment and combination of tunicamycin (an endoplasmic reticulum pathway activator) with Gilteritinib achieved the similar effect as treatment with Gilteritinib plus ATO. Conclusions Thus, ATO at low concentration potentiates Gilteritinib-induced apoptosis in FLT3-ITD positive leukemic cells via IRE1a-JNK signal pathway, targeting IRE1a to cooperate with Gilteritinib may serve as a new theoretical basis on FLT3-ITD mutant AML treatment.